Quantitative monitoring of corticosteroids in cosmetic products manufactured in Korea using LC-MS/MS - Nam, Yun Sik; Kwon, Il Keun; Lee, Yeonhee; Lee, Kang-Bong (ELSEVIER IRELAND LTD, 2012)
Some cosmetic products manufactured in Korea for the treatment of eczema, seborrhea and psoriasis have been suspected to contain anti-inflammatory corticosteroids such as prednisolone, hydrocortisone, betamethasone, dexamethasone and triamcinolone acetonide without these ingredients being indicated on the label. Due to their severe side effects such as permenent skin atopy, these corticosteroids have to be monitored in cosmetic products from a forensic point of view. Many cosmetic product samples (N = 65) have been collected from both local and online markets in Korea. The corticosteroid content of these samples was analyzed by LC-MS/MS with diagnostic ions (m/z). Linearity was studied with 0.1-10 mg/mL range in all corticosteroids. Good correlation coefficients (r(2) >= 0.997) were found and the limits of quantification were 4.68-7.97 ng/mL for each of the corticosteroids. At three different concentrations spanning the linear dynamic ranges, mean recoveries were 97.2-113.5% and precisions (RSD) for intra-day and inter-day analysis were less than 8.9%. Also, accuracy (Bias %) was less than 11.8%. The results showed that between 0.76-0.94 mg/g levels of prednisolone were detected in four cosmetic products and triamcinolone acetonide was detected with a concentration in the range of 11.5-272 mg/g in nine samples. This fact reveals that some manufacturers have arbitrarily added these corticosteroids in their cosmetic products without indicating them on the label. Thus, these cosmetic products have to be monitored and if proven illegal preparations removed from the market. (C) 2011 Elsevier Ireland Ltd. All rights reserved.
Keywords: TANDEM MASS-SPECTROMETRY; LIQUID-CHROMATOGRAPHY; CLOBETASOL PROPIONATE; DEXAMETHASONE; GLUCOCORTICOIDS; BETAMETHASONE; PLASMA; CORTISOL; DIFFERENTIATION; QUANTIFICATION